Pengaruh Effervescent Ekstrak Kulit Nanas dalam Menghambat Pertumbuhan Candida Albicans pada Resin Akrilik Heat Cured - Aldo Alveno; Meinar Nur Ashrin; Dian W Damaiyanti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Maintaining dentures is an important key. Pineapple peel extract containing bromelin enzyme as an antifungal might can be used as an alternative denture cleanser. Purpose: To know the difference of candida albicans growth in addition of pineapple peel extract effervescent. Materials and Methods: Heat-cured acrylic resin in 10x10x1 mm in size was used as sample which was soaked into pineapple peel extract effervescent for 5 minutes. There are 4 groups, group 1: sterile aquades as negative control; group 2: potassium monopersulfat, Sodium Hexametaphosphate effervescent as positive control; group 3: 3.5% in concentration; group 4: 7% in concentration. Data was analyzed by using oneway anova and post hoc analysis with LSD test. Result: There was a significant difference in total of candida albicans colony in each treatment group (P≤0,05). LSD test showed a significant difference in group 2 compared to group 4 and group 3 compared to group 4. Conclusions: Pineapple peelextract effervescent gave a significant difference of candida albicans colony growth and therefore can be used as an alternative denture cleanser.